Lipoxygenase LOX3 Is the Enigmatic Tocopherol Oxidase in Runner Bean (Phaseolus coccineus) - Jerzy Kruk; Paweł Jedynak; Sylwia Kędracka-Krok; Renata Szymańska; Michał Gabruk (MDPI AG, 2024)
Purification of extracts from the etiolated seedlings of runner bean (Phaseolus coccineus), coupled with mass spectrometry analysis of proteins revealed that the enzyme responsible for tocopherol oxidation activity is lipoxygenase, an enzyme known for enzymatic lipid peroxidation of unsaturated lipids. Biochemical analysis of the activity, along with the expression profile of three LOX isoforms (LOX1, LOX2, LOX3) in various parts of the etiolated seedlings, revealed that LOX3 was the major isoform expressed in the epicotyls, indicating that this isoform was responsible for the tocopherol oxidation activity; in the primary leaves, besides LOX3, the other two isoforms might have also contributed to the activity. The experiments performed in the model systems showed that unsaturated lipids were not required for the tocopherol oxidase activity, but that lipids were necessary to provide an optimal, hydrophobic environment of the substrate for the reaction. The experiments on lipoxygenase and tocopherol oxidase activities in the leaves of light-grown P. coccineus plants during aging and during storage of the extracts from etiolated seedlings showed that the activity of the first reaction decreased considerably faster than the latter, indicating different mechanisms of both reactions performed by the same enzyme. As LOX3 was shown to occur in the apoplast of the related species P. vulgaris, the question as to the physiological function of LOX3 in the tocopherol oxidation activity in P. coccineus is discussed.